Protective roles of free avian respiratory macrophages in captive birds - Mbuvi P. Mutua; Shadrack Muya; Muita M. Gicheru (Biological Research)
In the mammalian lung, respiratory macrophages provide front line defense against invading pathogens and particulate matter. In birds, respiratory macrophages are known as free avian respiratory macrophages (FARM) and a dearth of the cells in the avian lung has been purported to foreordain a weak first line of pulmonary defense, a condition associated with high mortality of domestic birds occasioned by respiratory inflictions. Avian pulmonary mechanisms including a three tiered aerodynamic filtration system, tight epithelial junctions and an efficient mucociliary escalator system have been known to supplement FARM protective roles. Current studies, however, report FARM to exhibit an exceptionally efficient phagocytic capacity and are effective in elimination of invading pathogens. In this review, we also report on effects of selective synthetic peroxisome proliferator activated receptor gamma (PPAR γ) agonists on non phlogistic phagocytic properties in the FARM. To develop effective therapeutic interventions targeting FARM in treatment and management of respiratory disease conditions in the poultry, further studies are required to fully understand the role of FARM in innate and adaptive immune responses.